The Effect of Exclusive Breastfeeding on the Nutritional Status of Mothers and Infants in the Working Area of Telaga Health Center - Indriyani Ali; Harismayanti; Ani Retni (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Low coverage of exclusive breastfeeding not only impacts infants but can also reduce the achievement of optimal nutritional status for mothers and infants during the breastfeeding period. Mothers and children are vulnerable to declining nutritional status. This is due to several factors, particularly the increased nutritional needs of mothers during pregnancy and breastfeeding, as well as the rapid growth and development of children aged 0–6 months. The study aimed to determine the effect of exclusive breastfeeding on the nutritional status of mothers and infants. The research design used a quantitative correlational cross-sectional method. The population in this study were all mothers with infants aged 0–6 months. The sample was drawn using a purposive sampling technique, resulting in 57 respondents. Data analysis used the Chi-square test with a significance level of 0.05. The results of the study showed that on average, 33 mothers (57.9%) had normal nutritional status, and 35 babies (61.4%) had normal nutritional status. There was an influence of Exclusive Breastfeeding on the Nutritional Status of Mothers and Babies with a p value of 0.000 < 0.05. It can be concluded that there is an influence of exclusive breastfeeding on the nutritional status of mothers and babies in the Telaga Health Center work area.